Improving Fiction Reading Comprehension through Metaverse Media-Assisted Reciprocal Teaching in Elementary School - Dhiyaa Yolanda; Nur Latifah (UIN Raden Mas Said Surakarta, Indonesia, 2026)
Reading comprehension is an important skill that needs to be developed from elementary school level because it helps students understand information and interpret the meaning of texts. However, some students still experience difficulties in comprehending fictional texts during the learning process. This study aims to examine the effect of the Reciprocal Teaching model assisted by metaverse media on elementary school students' fiction reading comprehension. This study used a quantitative approach with a quasi-experimental method using a non-equivalent control group design. Participants consisted of 58 fifth-grade elementary school students divided into an experimental group (29 students) and a control group (29 students). Data were collected through pretests and posttests using a reading comprehension test instrument. Data analysis was conducted using the Wilcoxon Signed Rank Test to determine improvements within groups and the Mann-Whitney U Test to examine differences between groups. The results showed a significant difference in reading comprehension between the experimental and control groups (p < 0.001). In addition, the calculation of the effect size showed a strong effect (r = 0.61). These findings indicate that the Reciprocal Teaching model assisted by metaverse media is effective in improving elementary school students' fiction reading comprehension.